2018
DOI: 10.22246/jikm.2018.39.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Recent RCT Research on the Effects of Acupuncture on Dementia - Based on a PubMed Search of Literature Published from 2000 to 2018

Abstract: The purpose of this study is to investigate recent clinical studies on the effects of acupuncture on dementia. Method: We searched RCTs (randomized controlled trials) using the database PubMed (2000-2018). Clinical RCT studies of acupuncture used to treat dementia in humans were included. Nine randomized controlled trials were included. Results: Various acupoints such as Baihui (GV20), Sishencong (EX-HN1), Fengchi (GB20), and Shenting (GV24) were used to treat symptoms. The studies reported a decrease in evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Using functional magnetic resonance imaging Zheng et al reported that acupuncture activated the sections in the brain that related to cognitive function in patients with AD [9]. Similarly, other studies mentioned the potential of acupuncture in the improvement of AD [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using functional magnetic resonance imaging Zheng et al reported that acupuncture activated the sections in the brain that related to cognitive function in patients with AD [9]. Similarly, other studies mentioned the potential of acupuncture in the improvement of AD [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted to verify the effect of Korean medicine treatment on AD. In the published studies of herbal medicine treatment for AD, case reports and the assessments of the effects of oriental medicine have been published [6,7], while in the studies of acupuncture treatment of AD, case reports and studies of acupuncture with magnetic resonance imaging scans have been published [8,9]. In addition, meta-analysis studies of the effect of acupuncture were also reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%